Stress analysis in oral obturator prostheses over parallel and tilted implants: photoelastic imaging - Pesqueira, Aldieris Alves [UNESP] (2013)
This study aimed to evaluate the stress distribution through the photoelastic method in implant-retained palatal obturators prostheses. Two photoelastic models with bucco-sinusal communication were fabricated, one model without implants and another with two parallel implants and one tilted in the molar region. A conventional obturator prosthesis and five implant-retained obturators dentures with different attachment systems were fabricated: OR, three individualized O-rings; BC, bar clip; BOC, implants splinted by bars associated with two O-rings positioned at the center of the bar; OD, implants splinted by bars associated with two O-rings positioned in distal cantilever; and BOD, implants splinted by bars with clips associated with two O-rings positioned in distal cantilever. Each assembly (model/attachment system/prosthesis) was positioned in a circular polariscope and a load of 100 N was applied on each implant. The results were obtained by observing the photographic record of the tensions in the photoelastic models resulting from the application of load. It can be observed that a larger amount of stress fringes on BC system. It was concluded that the attachment system has a direct influence on the stress distribution of implant-retained obturator prostheses, with the three individualized O-rings exhibiting the lowest stress values, and tilted implants presented a biomechanical behavior similar to parallel implants. (C) The Authors.